ANALISIS BAURAN PEMASARAN TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN RAUDHAH CHICKEN DI JALAN DURIAN PEKANBARU - Putri, Debora; Yusmini, Yusmini; Eliza, Eliza (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
This study aims to Analyze the marketing mix that influences consumer purchasing decisions Raudhah Chicken, Analyzing the relationship between the marketing mix of consumer purchasing decisions Raudhah Chicken. This research using purposive sampling method with the respondents of the study amounted to 90 respondents who have aged> 17 years, shop at Raudhah Chicken more than 1 times. The data were analyzed using Likert scale, validity test, reliability test and Cartesian diagram,Spearman rank correlation analysis.The results showed that of the five marketing mix variables, all of which are in the category of "influential". Correlation analysis of rank spearman that show relationship between marketing mix to consumer decision is positive and strong and significant (x = 0,01).Marketing mixed positive correlation coefficient (+), meaning the relationship of marketing mix with consumer decisions is the same direction so if the marketing mix is increased then consumer decisions will also increase.It is advisable For the Raudhah Chicken party to improve the mix of market such as: product, price, place, promotion,service and increase sales of chicken Raudhah so that consumrs will continue to shop and do not switch to another. Key words: Marketing mix, Consumer decision, Consumer, Raudhah Chicken